Preparation method and application for in-situ generation of organic-inorganic hybrid SEI layer in zinc ion battery
By using polysaccharide/polyacrylamide dual network hydrogel electrolyte in zinc ion batteries, the dendrite and corrosion problems during the cycling of zinc ion batteries are solved, and the cycle stability of the battery is improved and life span, the balance of zinc foil for water electrolyte is achieved, significantly improving the performance of the battery.
Patent Information
- Application Number
- CN202411414780.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
Zinc ion batteries often have dendrite and corrosion problems during the cycle process, which affects the cycle stability and life of the battery. The existing non-in-situ SEI layer is good at the beginning of the cycle but then fails, which cannot effectively solve the stability problem of zinc negative electrode. .
The organic-inorganic hybrid SEI layer is formed in situ in zinc ion battery by polysaccharide/polyacrylamide dual network hydrogel electrolyte, and the polysaccharide active functional groups are adsorbed on the surface of zinc foil, and combined with the reduction reaction of zinc salt anions to form C-F, O-C, The organic outer layer of O-S and the inorganic inner layer containing Zn-F, Zn-O, and Zn-S reduce the electrode-electrolyte interface impedance and maintain the balance of favorability of zinc foil.
It significantly reduces the electrode-electrolyte interface impedance, inhibits the hydrolysis reaction and dendritic growth of the zinc foil surface, improves the rate performance and cycle performance, and extends the cycle life of the battery. The capacity of zinc-vana battery is maintained at 0.2A/g for 370 cycles. The rate reaches 95.4%, and the capacity retention rate of 3000 cycles at 5A/g is about 100%.
Smart Images

Figure HDA0005079093120000011 
Figure HDA0005079093120000012 
Figure HDA0005079093120000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and specifically relates to a preparation method and application of an in-situ generated organic-inorganic hybrid SEI layer in a zinc ion battery. Background Art
[0002] Aqueous zinc-ion batteries have the following advantages: (1) High specific capacity (820 mAh g -1 ) and high volumetric capacity (5849 mAh cm -3 ); (2) abundant zinc resources; (3) low redox potential (-0.76V compared to standard hydrogen electrode); (4) intrinsic safety and environmental friendliness, zinc metal can be used directly as the negative electrode (Energy Environ. Sci. 2020, 13, 3330). The aqueous electrolyte used in aqueous zinc-ion batteries has the property of being intrinsically non-flammable, which is one of the determining factors for ensuring battery safety.
[0003] However, zinc negative electrodes often have problems such as dendrites and corrosion during battery cycling, which seriously affect the cycle stability of the battery and reduce the battery life. Recently, researchers have tried to alleviate the dendrites and corrosion of zinc negative electrodes by adding electrolyte additives, but none of them are very effective.
[0004] Constructing SEI (Solid Electrolyte Interphase) on zinc foil negative electrode is a simple and effective method, which is mainly divided into two types: constructing an artificial SEI interface layer and constructing an SEI layer in situ during battery cycling (Nano Energy 2023, 117, 108799). However, most of the literature reports on artificial SEI interface layers constructed non-in situ. Usually, this non-in situ artificial SEI layer has good performance at the beginning of the cycle, such as hydrophobicity, but as the battery cycles, the non-in situ artificial SEI layer often fails and loses its original protective effect.
[0005] In-situ construction of the SEI interface layer can not only be well compatible with the electrode and electrolyte interface, but also can be continuously strengthened during the cycle process, continuously maintain its function, and improve the cycle life of the battery (Adv. Energy Mater. 2023, 13, 2302749). Therefore, in-situ construction of the SEI interface layer is of great significance for further improving the performance of zinc-ion batteries, and it is worth further exploration in this direction. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to generate an organic-inorganic hybrid SEI layer in situ by using a double network gel electrolyte constructed by a polymer polysaccharide additive in a zinc ion battery, which is of great significance for promoting the industrialization of zinc ion batteries.
[0007] A preparation method for in-situ generation of an organic-inorganic hybrid SEI layer in a zinc ion battery, using a polysaccharide / polyacrylamide double network hydrogel electrolyte as the electrolyte of the zinc ion battery, further assembled with a positive electrode sheet and a negative electrode sheet into a zinc ion battery, wherein the zinc ion battery generates an organic-inorganic hybrid SEI layer in-situ at the negative electrode during the charge and discharge cycle.
[0008] Preferably, the polysaccharide structure contains sulfonic acid groups or sulfate groups, and the polysaccharide includes carrageenan and its analogs; wherein the carrageenan type is one or more of κ-type, ι-type, λ-type, γ-type, ν-type, ξ-type, and μ-type.
[0009] Preferably, the double network gel electrolyte salt component is a fluorine-containing organic zinc salt, specifically one or more of zinc trifluoromethanesulfonate, zinc bis(trifluoromethylsulfonyl)imide, and zinc bis(trifluoroethylsulfonyl)imide.
[0010] In the present invention, an organic-inorganic hybrid SEI layer is generated in situ in a zinc ion battery, wherein the outer portion of the SEI layer is mainly composed of organic components containing three chemical bonds of CF, OC, and OS, and the inner portion of the SEI layer is mainly composed of inorganic components containing three chemical bonds of Zn-F, Zn-O, and Zn-S.
[0011] The formation mechanism of the organic-inorganic hybrid SEI layer is as follows: First, the active functional groups of polysaccharides are adsorbed on the surface of zinc foil to build an interface protection layer, which provides stable interface conditions for the subsequent formation of the organic-inorganic hybrid SEI layer; then, during the battery cycle, while the zinc ion redox reaction occurs on the zinc anode interface, the anion groups of the organic zinc salt and the active functional groups of the polysaccharide are also partially reduced, forming a uniform and dense interface layer containing three chemically bonded inorganic components of Zn-F, Zn-O, and Zn-S on the zinc anode interface, i.e., an inorganic-rich SEI inner layer, in which Zn-F comes from the reduction of zinc salt anions, and Zn-O and Zn-S come from the co-reduction of zinc salt anions and polysaccharide active functional groups. At the same time, the unreduced zinc salt anion groups and polysaccharides form an organic-rich outer layer containing three chemically bonded organic components of CF, OC, and OS through adsorption, in which CF comes from zinc salt anions, and OC and OS come from zinc salt anions and polysaccharides. Finally, an organic-inorganic hybrid SEI layer is formed at the electrode-electrolyte interface.
[0012] The formation of this organic-inorganic hybrid SEI layer, on the one hand, greatly reduces the electrode-electrolyte interface impedance and induces uniform zinc deposition. On the other hand, it enables the zinc foil to maintain a balance of affinity and repellency to the aqueous electrolyte (the contact angle value is maintained at around 70-90o during the cycle), greatly avoiding the hydrolysis side reaction of the hydrophilic interface system, inhibiting corrosion and by-products, and improving the battery's rate performance and cycle performance.
[0013] In the present invention, an organic-inorganic hybrid SEI layer is generated in situ in a zinc ion battery, and the voltage window of the zinc ion battery charge and discharge cycle is 0.2 to 1.6 V, and the charge and discharge current density is 0.1 to 20 mA cm -2 .
[0014] In the present invention, an organic-inorganic hybrid SEI layer is generated in situ in a zinc ion battery, and the negative electrode sheet of the zinc ion battery is any one of zinc foil and zinc sheet.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) The present invention greatly reduces the electrode-electrolyte interface impedance by in-situ electrochemically generated organic-inorganic hybrid SEI layer, induces uniform zinc deposition, and improves rate performance and low-temperature performance.
[0017] (2) The present invention uses an organic-inorganic hybrid SEI layer generated in situ by electrochemical means to maintain a balance of affinity and repellency of the zinc foil to the aqueous electrolyte, effectively inhibit the hydrolysis reaction on the surface of the zinc foil, prevent the growth and corrosion of dendrites during circulation, greatly alleviate the capacity decay of the zinc ion battery, and extend the cycle life of the battery.
[0018] (3) The present invention uses an organic-inorganic hybrid SEI layer generated in situ by electrochemical means to enable the zinc-vanadium battery to cycle 370 times at 0.2 A / g, with a capacity retention rate of 95.4% and a cycle time of 1484 h;
[0019] After 3000 cycles at 5A / g, the capacity retention rate is about 100%; the above excellent electrochemical performance shows that the organic-inorganic hybrid SEI layer generated in situ by electrochemistry plays a practical and effective role, greatly enhancing the cycle stability of zinc-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 . Stress-strain curve of gel electrolyte in Example 4
[0021] Figure 2 Room temperature ionic conductivity of different gel electrolytes in Example 1, Example 2, and Example 3
[0022] Figure 3. Ionic conductivity diagram of CG / PAM double network gel electrolyte at different temperatures in Example 1
[0023] Figure 4 . Tafel curves of three gel electrolytes in Example 5
[0024] Figure 5 . LSV curves of CG / PAM gel electrolytes with different CG contents in Example 5
[0025] Figure 6 Example 5 Coulombic efficiency diagram of Zn / / SS battery assembled with different electrolytes
[0026] Figure 7 Example 5 Cycling curves of Zn / / Zn symmetric batteries assembled with different electrolytes
[0027] Figure 8 Example 5 Photographs of zinc foil after cycling of Zn / / Zn symmetric batteries assembled with different electrolytes
[0028] Fig. 9 Example 5 SEM images of zinc foil after cycling of Zn / / Zn symmetric batteries assembled with different electrolytes
[0029] Fig.10 Example 5 XRD patterns of zinc foil after cycling of Zn / / Zn symmetric batteries assembled with different electrolytes
[0030] Fig.11 Example 5 EIS graphs of Zn / / Zn symmetric batteries assembled with different electrolytes before and after cycling
[0031] Fig.12 XPS profile of the zinc foil surface after cycling of the Zn / / Zn symmetric battery assembled with the CG / PAM dual network gel electrolyte in Example 5
[0032] Fig.13 .Contact angle of zinc foil of Zn / / Zn symmetric battery assembled with different electrolytes in Example 5 at different cycle numbers
[0033] Fig.14 CV curves of zinc-vanadium full battery assembled with CG / PAM double network gel electrolyte at different scan rates in Example 6
[0034] Fig.15 . Rate performance of zinc-vanadium full batteries assembled with different electrolytes in Example 6
[0035] Fig.16 .Charge and discharge curves of zinc-vanadium full battery assembled with CG / PAM double network gel electrolyte at different current densities in Example 6
[0036] Fig.17Cycling curves of zinc-vanadium full batteries assembled with different electrolytes at 0.2 A / g in Example 6
[0037] Fig.18 Cycling curves of zinc-vanadium full batteries assembled with different electrolytes at 5A / g in Example 6
[0038] Fig.19 XRD patterns of zinc foil after cycling of zinc-vanadium full batteries assembled with different electrolytes in Example 6
[0039] Fig. 20 SEM images of zinc foil after cycling of zinc-vanadium full batteries assembled with different electrolytes in Example 6
[0040] Fig.21 Cycling curve of zinc-vanadium full battery assembled with CG / PAM double network gel electrolyte at -40°C in Example 6
[0041] Fig. 22 Cycling curve of zinc-vanadium soft pack battery assembled with CG / PAM double network gel electrolyte in Example 6
[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings. DETAILED DESCRIPTION
[0043] The following examples are intended to illustrate the present invention rather than to further limit the present invention.
[0044] Example 1
[0045] Preparation of carrageenan / polyacrylamide (CG / PAM) double network hydrogel electrolyte:
[0046] First, carrageenan (125 mg, 2.5% content) was added to deionized water (5 mL), stirred at 80 ° C until completely dissolved to obtain a uniform sol. Then, monomer acrylamide (1.67 g), zinc salt zinc trifluoromethanesulfonate (3.63 g), crosslinker N, N'-methylenebisacrylamide (4 mg), and photoinitiator 2-oxoglutaric acid (4 mg) were added in sequence, and then stirred at 80 ° C until completely dissolved. Then it was transferred to a glass mold and placed in a refrigerator at 4 ° C for 1 hour. Finally, it was placed under ultraviolet light for photopolymerization for 2 hours to obtain a CG / PAM double network gel electrolyte with a carrageenan content of 2.5%. Below, unless otherwise specified, the carrageenan content of the CG / PAM double network gel electrolyte is 2.5%.
[0047] Example 2
[0048] Preparation of a double network gel electrolyte with different carrageenan concentrations:
[0049] Referring to the preparation method of Example 1, the addition amount of carrageenan was changed to 1.5% or 0.5%.
[0050] Example 3
[0051] Preparation of a PAM gel electrolyte:
[0052] The preparation method of Example 1 was followed without adding carrageenan.
[0053] Example 4
[0054] Mechanical properties test of gel electrolyte:
[0055] The inventors further conducted mechanical tensile tests on the gel electrolytes prepared in Examples 1, 2 and 3 at room temperature. Figure 1 Figure 3 is the stress-strain curve of PAM and CG / PAM gel electrolyte. It can be seen from the figure that the fracture stress and strain of single network PAM gel are the smallest. With the increase of CG content, the maximum stress and strain gradually increase. When the CG content is 2.5%, the fracture stress of CG / PAM reaches 134 kPa and the fracture strain is 565%. In general, the addition of CG helps to improve the mechanical toughness of the gel electrolyte.
[0056] Example 5
[0057] Assembly and testing of Zn / / Zn symmetric cells and Zn / / SS asymmetric cells:
[0058] A Zn / / Zn symmetric battery can be prepared by using two zinc foils as pole pieces and combining them with the gel electrolyte or liquid electrolyte prepared in Example 1, Example 2 and Example 3, respectively. Similarly, a Zn / / SS asymmetric battery can be prepared by using zinc foil and stainless steel foil (SS) as pole pieces and combining them with the gel electrolyte or liquid electrolyte prepared in Example 1, Example 2 and Example 3, respectively.
[0059] The impedance curve of the Zn / / Zn symmetric battery was tested and the ionic conductivity of various electrolytes was calculated. The results are as follows: Figure 2 As shown. Among them, the ionic conductivity of the liquid is the highest, followed by PAM gel electrolyte, and then CG / PAM dual network gel electrolyte. It is worth noting that the more CG is added, the lower the ionic conductivity. This may be because the more CG content, the stronger its interaction with water, turning more free water into bound water, thereby reducing the ionic conductivity of the gel electrolyte.
[0060] The inventors further tested the low temperature ionic conductivity of the CG / PAM double network gel electrolyte prepared in Example 1. Figure 3As shown in the figure, the ionic conductivity of CG / PAM double network gel electrolyte was tested at -40℃, -20℃, 0℃, 30℃, and 50℃. The results showed that the ionic conductivity was negatively correlated with the temperature. The ionic conductivity was the highest at 50℃, which was 35.7mS / cm. At -40℃, it could still maintain 3.55mS / cm, which can meet the normal operation requirements of the battery at low temperatures.
[0061] Figure 4 The Tafel curve shows that the CG / PAM gel electrolyte has a higher corrosion potential and a smaller corrosion current than the other two groups, which indicates that the CG / PAM gel electrolyte has better electrochemical stability and is more conducive to stable operation of the battery.
[0062] Test the LSV curve of Zn / / SS asymmetric battery, such as Figure 5 As shown in the figure, with the increase of CG addition, the hydrogen evolution current of the double network gel electrolyte becomes smaller, indicating that the addition of CG is beneficial to inhibiting the hydrogen evolution activity of the electrolyte and reducing the occurrence of hydrogen evolution.
[0063] In addition, the coulombic efficiency of Zn / / SS batteries assembled with different electrolytes was tested. The current density and surface capacity adopted were 1 mA cm -2 and 0.5 mAh cm -2 The experimental results are as follows Figure 6 As shown, it can be found that the liquid electrolyte and PAM gel electrolyte groups exhibit lower Coulombic efficiency and greater fluctuations at the beginning of the cycle; in contrast, the CG / PAM dual network gel electrolyte has an average Coulombic efficiency of 99.7% over more than 600 cycles, showing a very high deposition / stripping efficiency.
[0064] In addition, the charge-discharge cycles of Zn / / Zn batteries assembled with different electrolytes were tested with a current density and surface capacity of 1 mA cm -2 and 1mAh cm -2 .like Figure 7 As shown in the figure, both the liquid electrolyte group and the PAM gel electrolyte group experienced polarization and failure within 100 hours; on the contrary, the CG / PAM group can be stably cycled for more than 500 hours, which is much better than the liquid electrolyte group and the PAM gel electrolyte group.
[0065] Figure 8 The surface morphology of the zinc foil after cycling is shown. It can be found that the surface of the zinc foil of the CG / PAM group after cycling is intact and smooth, while the surface of the zinc foil of the PAM group after cycling is corroded, and the zinc foil of the liquid electrolyte group after cycling is even perforated. The results show that the CG / PAM gel electrolyte protects the zinc foil from corrosion well during the battery cycling process, while the other two groups of electrolytes will cause corrosion to the zinc foil.
[0066] The microstructure of the zinc foil after cycling in the three electrolyte groups was studied by SEM. Fig. 9 As shown in the figure, the zinc foils in the CG / PAM group all showed good flatness and uniform deposition, while the zinc foils in the other two groups showed dendrites and corrosion. The cross-sectional SEM image also proved this point, that the zinc foil surface in the CG / PAM group was smoother and denser, while the other two groups showed obvious dendrite protrusions.
[0067] The inventors further tested the XRD patterns of the zinc foil surface after cycling in the three electrolyte groups, and the results were as follows: Fig.10 As shown in the figure, the byproduct Zn appeared in both the liquid electrolyte group and the PAM group zinc foil. x (OTF) y (OH) 2x-y The peak of nH2O indicates that these two groups of electrolytes have strong side reactions during cycling. On the contrary, the zinc foil of the CG / PAM group has almost no by-product peak, which shows that the CG / PAM gel electrolyte can effectively inhibit the occurrence of side reactions during battery cycling, prevent the generation of by-products, and improve the performance of the battery.
[0068] The inventors further tested the EIS spectra of the Zn / / Zn symmetric battery assembled with three electrolytes in Example 5 before and after cycling. The results are as follows: Fig.11 As shown. R of CG / PAM group before cycling ct The impedance of the PAM group was 199Ω after cycling, and the impedance of the liquid group even rose to 570Ω.
[0069] The inventors further performed XPS profile tests on the zinc foil after cycling in the CG / PAM group Zn / / Zn symmetric battery in Example 5, and tested the C1s, F1s, O1s, and S2p element spectra on the zinc foil surface, at 5nm and 10nm depth, and further obtained specific information on the SEI. The results are as follows: Fig.12As shown. From the C1s spectrum, it can be seen that on the surface of the zinc foil, the main groups are CC / CH, CO, and OC=O groups. When going deep into the SEI layer, it is found that the peak areas of these groups gradually decrease, indicating that these organic groups are mainly distributed outside the SEI layer. When going deep into the SEI layer, the organic components gradually decrease. From the F1s, O1s, and S2p spectra, it can be seen that the outside of the SEI layer is mainly composed of organic groups such as CF, OC, and OS. When going deep into the SEI layer, the content of organic groups such as CF, OC, and OS gradually decreases, while inorganic components such as Zn-F, Zn-O, and Zn-S gradually increase and become the main components of the inner SEI layer. In summary, the SEI is a SEI layer hybridized with organic and inorganic components, and the outer layer of the SEI is mainly composed of organic components, while the inner layer is mainly composed of inorganic components.
[0070] The inventors further tested the contact angle of zinc foil after the liquid electrolyte was cycled for 10 and 200 times. The results are as follows: Fig.13 As shown in the figure, the contact angles of the two zinc foils in the CG / PAM group after cycling are similar, while the contact angles of the two zinc foils in the PAM group and the liquid electrolyte group are quite different. The contact angle after 200 cycles decreases significantly, indicating that no protective SEI layer is generated on the surface of the zinc foil in the PAM group and the liquid electrolyte group. During the cycling process, the surface of the zinc foil is corroded and a large amount of by-products are generated, which causes the hydrophilicity of the zinc foil surface to increase.
[0071] Example 6
[0072] Assembly and testing of a zinc-vanadium battery:
[0073] Firstly, manganese vanadate (MnVO@CNT) cathode material was mixed with PVDF as a binder, conductive carbon black as a conductive agent, N-methylpyrrolidone as a solvent, and stainless steel foil as a current collector to prepare a cathode electrode sheet (MnVO@CNT loading 2-6 mg / cm 2 ); then assemble the positive electrode sheet and the zinc foil negative electrode sheet with the gel electrolyte or liquid electrolyte in Example 1, Example 2 and Example 3 to obtain a zinc-vanadium battery.
[0074] The inventors further tested the CV curve of the zinc-vanadium battery assembled with the CG / PAM gel electrolyte prepared in Example 1, with a voltage range of 0.2V to 1.6V and scan rates of 0.1, 0.2, 0.5, and 1mV / s, respectively. The results are as follows: Fig.14 It can be seen that at different scan rates, the CG / PAM group zinc-vanadium batteries show two pairs of obvious redox peaks, among which the peak near 0.6V corresponds to V 4+ / V 3+ The peak near 1.0V corresponds to V 5+ / V 4+of redox.
[0075] The inventors further tested the rate performance of the zinc-vanadium battery assembled with three electrolytes in Example 5 and the charge and discharge curves of the CG / PAM zinc-vanadium full battery. Fig.15 , Fig.16 As shown, when the current density is 0.1, 0.2, 0.5, 1, 2, and 5 A / g, the discharge specific capacity of the CG / PAM group zinc-vanadium full battery is 341.4, 321.7, 292.6, 266.6, 227.3, and 155.6 mAh / g, respectively, which is higher than that of the PAM group on the whole, and when the current density is large, the rate performance is better than that of the liquid electrolyte group.
[0076] The inventors further tested the cycling performance of the three electrolyte zinc-vanadium full batteries assembled in Example 5. Fig.17 The figure shows the cycle curves of zinc-vanadium full batteries based on three electrolytes at a low current density of 0.2A / g. After 370 cycles of the CG / PAM group zinc-vanadium full battery, the capacity retention rate is still 95.4%, and the average coulombic efficiency is as high as 99.98%; in contrast, after 370 cycles of the PAM group, the capacity retention rate is only 78.6%; after 63 cycles of the liquid electrolyte group, the capacity retention rate is 64.7%, and then the battery fails due to short circuit.
[0077] Fig.18 The cycling curves of zinc-vanadium full batteries based on three electrolytes at 5A / g show that after 3000 cycles of the CG / PAM group zinc-vanadium full battery, the capacity has almost no attenuation, the capacity retention rate is 100%, and the average coulombic efficiency is about 100%; in contrast, after 1700 cycles of the PAM group, the capacity retention rate is only 75.5%; after 1700 cycles of the liquid electrolyte group, the capacity retention rate is 38%. The above zinc-vanadium full battery cycling data show that the CG / PAM dual network gel electrolyte is conducive to the long life of the battery and reduces the attenuation of capacity.
[0078] Fig.19 XRD patterns of zinc foil after cycling of full batteries assembled with three electrolytes. The byproduct Zn appeared in both the liquid electrolyte group and the PAM group zinc foil. x (OTF) y (OH) 2x-y The peak of nH2O indicates that more side reactions occur in the two groups of electrolytes during cycling. On the contrary, the zinc foil of the CG / PAM group has no by-product peak at all, indicating that the CG / PAM gel electrolyte can effectively inhibit the occurrence of side reactions during battery cycling, prevent the generation of by-products, and improve the performance of the battery.
[0079] Fig. 20The SEM images of zinc foil after full battery cycling assembled with three electrolytes are attached with photos of zinc foil. In the picture, the surface of zinc foil in the CG / PAM group is relatively smooth, without obvious dendrites and corrosion; on the contrary, zinc foil in the liquid electrolyte group and PAM gel electrolyte group is severely corroded, with pitted surfaces observed, which is very uneven.
[0080] Then, the inventor assembled the CG / PAM double network gel electrolyte prepared in Example 1 to test the low temperature cycling performance of the zinc-vanadium full battery. The cycling performance of the battery was tested at -40°C and 0.2A / g. The results are as follows: Fig.21 The battery shown has an initial discharge specific capacity of 321.2 mAh / g, and a capacity retention rate of 83.2% after 500 cycles, indicating that the CG / PAM electrolyte also has excellent performance at low temperatures, meeting the high performance and long-term operation requirements of the battery.
[0081] Finally, the inventors assembled zinc-vanadium soft-pack batteries (CG / PAM double network gel electrolyte prepared in Example 1) Fig. 22 ), the initial capacity of the battery is 25mAh, and the surface capacity reaches 1.6mAh / cm 2 After 100 cycles, the capacity retention rate is still 85.6%, and the average coulombic efficiency reaches 99.87%. This result shows that the SEI layer generated in situ by the CG / PAM double network gel electrolyte is effective in both button cells and large soft pack batteries, and is expected to be industrialized.
[0082] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing an in-situ generated organic-inorganic hybrid SEI layer in a zinc ion battery, characterized in that: The polysaccharide / polyacrylamide double network hydrogel electrolyte is used as the electrolyte of the zinc ion battery, and is further assembled with the positive electrode sheet and the negative electrode sheet into a zinc ion battery. During the charge and discharge cycle of the zinc ion battery, an organic-inorganic hybrid SEI layer is generated in situ at the negative electrode.
2. The method for preparing the organic-inorganic hybrid SEI layer according to claim 1, characterized in that: The outer part of the SEI layer is mainly composed of organic components containing three chemical bonds: CF, OC, and OS, while the inner part of the SEI layer is mainly composed of inorganic components containing three chemical bonds: Zn-F, Zn-O, and Zn-S.
3. The method for preparing the organic-inorganic hybrid SEI layer according to claim 1, characterized in that: The polysaccharide structure of the double network hydrogel electrolyte contains sulfonic acid groups or sulfate groups, and the polysaccharide includes carrageenan and its analogs.
4. The method for preparing the organic-inorganic hybrid SEI layer according to claim 1, characterized in that: The salt component of the double network gel electrolyte is a fluorine-containing organic zinc salt, including one or more of zinc trifluoromethanesulfonate, bis(trifluoromethylsulfonyl)imide zinc, and bis(trifluoroethylsulfonyl)imide zinc.
5. A method for preparing an in-situ generated organic-inorganic hybrid SEI layer in a zinc ion battery, characterized in that: The charging voltage window of the zinc ion battery charge and discharge cycle is 0.2~1.6V.
6. The method for preparing the organic-inorganic hybrid SEI layer according to claim 1, characterized in that: The negative electrode plate of the zinc ion battery is any one of zinc foil and zinc sheet.
7. A use of the organic-inorganic hybrid SEI layer according to any one of claims 1 to 6, characterized in that: Used as zinc ion batteries and zinc metal energy storage devices.
Citation Information
Cited By
Zinc ion battery electrolyte with in-situ induced double-layer solid electrolyte interface and application of zinc ion battery electrolyte
CN121035381A
Preparation method of double-network hydrogel electrolyte containing composite zinc salt
CN122136187A